Analysis and Design of the Water Distribution Network For Teeba Area, Nablus - Ranin Abu Gharbieh (My University, 2016)
Water is the most important substance for human body and every living organism to survive. It is everywhere we look. Water is in the ground and in the air that we breath. All animals, plants and humans need water to survive. Water has formed our earth since it began. It also prevents the earth from becoming too hot or too cold. Water never disappears. We use the same water over and over again. In addition water is essential for industrial, agricultural, touristic, and domestic usages. Since Teeba area has a branched network which is not practicle, a distribution network must be designed to efficiently supply water. The start of the work will require collecting data for the study area, such as the contour map, plans of existing and proposed road network, building regulations, the current distribution of houses, rates of water consumption and water supply, water sources, land use (commercial, agricultural, residential, or industrial use) and Population data. The needed data about the area will be collected from several sources and with the assistance of official institutions such as Nablus Municipality and Palestine Central Bureau of Statistics (PCBS). These data will be analyzed through employing engineering software such as WaterCAD, GIS ArcMap, AutoCAD and Excel.In order to efficiently use WaterCAD in the design of the water distribution network the hydraulic concepts related to this topic will be viewed in this report. The design was prepared under steady state and transient conditions in order to ensure that the water will neither exceed the maximum values of constraint of pressure and velocity in the peak hours of consumption through the day nor falling under the minimum values of constraint of pressure and velocity in the minimum hours of consumption through the night

. . . . .   . ( ) . . WaterCAD ArcMap Excel . WaterCAD . .
Analysis and Design of the Water Distribution Network For Teeba Area, Nablus